O "outro" sob o olhar cristão: representação dos judeus na disputa de Tortosa (Hispânia, 1º quarto do século XV) - Freitas, Jordânia Lopes de (2015)
This research aims to identify the reasons why Benedict XIII and the converted Jew, Jerome of Santa Fe, to perform the Dispute of Tortosa in 1413-14. It points out that the Jews of the Aragonese communities were victims of religious intolerance and are considered infidels, sinners, greedy and usury practitioners. In the Christian story of the Dispute of Tortosa, written by the papal scribe, there is opposition to Jewish polemicists and authority of the writings of the Talmud, which was seen as a literature in which one could find the Christian truth and attest to Messiah's coming. In the investigation of this religious conflict occurred in the kingdom of Aragon, makes use of a methodology which is based on Discourse Analysis and the theoretical assumption Roger Chartier about the representation of Christian discourse and how it was received by the Jews. Points as results Jerome's speech of Santa Fe, with the support of Benedict XIII, was given in an attempt to dissuade Jews, by denigrating the Talmud, about the legitimacy of the Catholic religion with a view to affirming the Christian identity. The Jerome speech was challenged by participants in the debate rabbis and Jewish response, referring to the Christian critique, it was presented with the objective of minimizing the devastating effects to the Jewish belief.